أهمية التعزيز النفسي وأثره على التحصيل اللغوي السنة الرابعة المتوسط أنموذجا - عبد اللاوي, محدة, سارة أنفال (University of El-oued, 2021)
الملخص: الملخص تناولنا في موضوع المذكرة "أهمية التعزيز النفسي وأثره على التحصيل اللغوي – السنة الرابعة المتوسط أنموذجا" وهذا ما حثنا إلى محاولة إجراء هذا البحث بين المعلم والتلميذ داخل الصف الدراسي وتوظيفه في العملية التعليمية وما يحققه المعلم مع تلاميذه من معززات و مكافآت إيجابية وللإحاطة بهذا الموضوع قمنا بتقسيم الدراسة إلى فصلين نلخص محتواها الآتي: الفصل الأول: وقمنا فيه بالتعريف بماهية المعلم وأثره في عملية التعليم المبحث الاول: من حيث تحديد ( مفهوم المعلم , خصائصه وسماته, دور المعلم في الأزمات والظروف الصفية سبل الارتقاء بمهنة التعليم) أما المبحث الثاني: (مفهوم التعزيز, التعزيز في علم النفس, أشكال المعززات, أهمية التعزيز وأثره ) نستنتج أن المعلم يعد من أهم أركان العملية التعليمية وهو الدور الفاعل والمكون لتكوين التلاميذ الفصل الثاني: وعرضنا من خلاله النتائج الاولية للدراسة في جداول بعد أن قمنا بتحديد مختلف التكرارات والنسب المئوية إلى جملة من النتائج المهمة والتي تؤكد على أن أغلبية الاساتذة الذين يعتمدون على أساليب تتسم باشتراك التلاميذ في العملية التعليمية وكذا التشجيع العمل الشخصي ومكافئة سلوكات التلاميذ التي تساعد على السير الحسن لعملية التعليم داخل القسم. Résumé : فرنسية أو انجلزية Abstract On the subject of the memorandum, we dealt with “the importance of psychological reinforcement and its impact on linguistic achievement – the fourth intermediate year as a model” and this is what prompted us to try to conduct this research between the teacher and the student in the classroom and employ it in the educational process and what the teacher achieves with his students of positive reinforcements and rewards. By dividing the study into two chapters, we summarize the following content: The first chapter: In it, we defined the nature of the teacher and its impact on the education process. The first topic: In terms of defining (the concept of the teacher, its characteristics and traits, the teacher’s role in crises and classroom conditions, ways to advance the teaching profession) As for the second topic: (the concept of reinforcement, reinforcement in psychology, forms of Reinforcers, the importance of reinforcement and its impact) We conclude that the teacher is one of the most important pillars of the educational process, which is the active and component role in the formation of students. Chapter Two: We presented the preliminary results of the study in tables, after we determined the various frequencies and percentages, to a number of important results, which confirm that the majority of teachers who rely on methods characterized by the participation of students in the educational process, as well as encouragement of personal work and rewarding students’ behaviors that help to Good conduct of the education process within the department.
Keywords: renforcement psychologique - réussite linguistique; التعزيز النفسي- التحصيل اللغوي